Integrasi Islam Dan Ilmu Pengetahuan - ., Ika; ., Ani Fitriyani; ., Dita Adellia Nabilla Siva (CV. ITTC INDONESIA, 2023)
The dichotomization of science and religion is actually a classic and prolonged problem, but along with changing paradigms and the development of scientific mastery in all fields, opportunities for the integration of science have opened wide. In fact, the sources of knowledge are integrated from the three major schemes, namely, natural sciences, social sciences, and humanities which actually originate from an integrative science building, namely the Qur'an and Hadith. In the Islamic concept, science begins with knowledge which is a manifestation of thoughts, feelings, beliefs and desires. However, in the western concept, the dichotomization of science is still seen with the separation between science and technology and IMTAQ, but this dichotomization does not last long, because it is increasingly clear that the development of science leads to one source, namely Allah SWT, so that it can be concluded that all branches of knowledge and knowledge contained in this universe is a unity of Islam, the wider the control, the more narrow the understanding.